2012
DOI: 10.1159/000338254
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Hardware and Surgical Complications with Deep Brain Stimulation Based on Diagnosis and Lead Location

Abstract: Introduction: Deep brain stimulation is the most frequently performed neurosurgical procedure for movement disorders. This procedure is well tolerated, but not free of complications. Analysis of hardware complications based on patient diagnosis and lead location could prove valuable in recognizing potential pitfalls and patients at higher risk. Methods: This review analyzes the most common surgery-related complications that may occur based on diagnosis and lead location. Patients were categorized based on diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 58 publications
1
24
1
2
Order By: Relevance
“…Sixel-Doring et al [26] in turn found that age, gender, disease duration, disease severity, hypertension and diabetes were not statistically more likely to cause infection in their PD population. Finally, Falowski et al [27] felt that surgical indications for ET and dystonia raised the risk of infection, whereas Piacentino et al [12] felt that the risk was higher with PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sixel-Doring et al [26] in turn found that age, gender, disease duration, disease severity, hypertension and diabetes were not statistically more likely to cause infection in their PD population. Finally, Falowski et al [27] felt that surgical indications for ET and dystonia raised the risk of infection, whereas Piacentino et al [12] felt that the risk was higher with PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…DBS also requires specific programming and additional operations for battery changes, in addition to being a costly device. 10,11,22 Typically, both destructive and nondestructive procedures have been beneficial in~40-60% of medically refractory OCD patients. 6,7,9,17,[23][24][25][26][27] Compared with conventional radiofrequency thermal capsulotomy or gamma capsulotomy, MRgFUS enabled us to create an exact and accurate lesion in the pre-planned target because of the real-time, closed-loop monitoring of the MR thermometry and sequential MR images.…”
Section: Discussionmentioning
confidence: 99%
“…48 Lead fractures and other hardware-related issues are not uncommon. 49 A wide range of neurologic and neuropsychological adverse effects has been reported with deep-brain stimulation. Some of these effects are related to device implantation and may require electrode relocation or, in some cases, may be permanent.…”
Section: Inic a L Usementioning
confidence: 99%